A trilingual policy’s dominant skills discourse, embodied theory of language(s) and teaching approaches: An analysis of/for university policy - Knott, Anne (South African Journal of Higher Education, 2016)
In a post-apartheid context requiring enabling policy frameworks to transform practices, I draw from pertinent national documents, the research literature and theoretical frameworks to analyse and critique a comprehensive university’s language policy for the presence/absence of discourses of literacies, theories of language(s) and teaching approaches. My analysis shows that a limited skills discourse of literacies embodied in a theory of language as a transparent, autonomous and singular, whole bounded system of discrete elements predominates. This skills discourse conceptualises ‘multilingual literacies’ as additive sets of linguistic and cognitive ‘skills’ situated in individuals and in terms of ‘functional’ or ‘situational’, ‘purposeful communication’ and ‘assimilationist’ socialisation approaches to teaching. While the policy designers take up sociopolitical discourses inscribed in national policies, these and its situational approaches are decoupled from a discourse of ‘multilingual literacies’ as ‘social practices’. I therefore argue that the policy cannot enable critical academic literacy approaches and accord with its guiding principles ‘to promote diversity’ and ‘be academically justifiable’ and ‘inclusive’. Moreover, I recommend that participants work meaningfully with each other to become critically aware of the discourses that they inhabit in order to enact more nuanced, comprehensive and integrated views of language(s), literacies and literacies pedagogy in policies and practices.